Analysis of Factors Affecting the Rupiah Exchange Rate Against the US Dollar 2000-2022 - I Putu Geri PURNAWAN; Dewa Putu Yudi PARDITA; Ita Sylvia Azita AZIZ (Loka: Journal Of Environmental Sciences, 2023)
Purpose:This research analyzes the factors influencing the rupiah exchange rate against the US dollar. This research was conducted to analyze the factors that influence the Rupiah exchange rate against the United States Dollar for the 2020-2022 periodMethodology:This research is based on secondary data, specifically time series data, obtained from reputable sources such as the websites of the Ministry of Trade of the Republic of Indonesia, Bank Indonesia, and the Central Statistics Agency. The data were meticulously processed using the robust method of multiple linear regression analysis, ensuring the reliability and validity of the findings.Findings:The results of the research show that inflation has a positive effect and a significant effect on the Rupiah exchange rate, Exports have a negative effect and no significant effect on the Rupiah exchange rate, Imports have a positive effect and have no significant effect on the Rupiah exchange rate, Foreign exchange reserves have a positive effect and have a significant effect on the Rupiah exchange rate Simultaneously or simultaneously Inflation, Exports, Imports and Foreign Exchange Reserves have a significant effect on the rupiah exchange rate.Implication:Inflation, exports, imports and foreign exchange reserves influence the rupiah exchange rate against the US dollar. Inflation has a positive impact, while exports have a negative impact, and imports are insignificant. Foreign exchange reserves provide a significant positive impact.